The Economic Position of First and Second Generation Immigrants in Canada - Lu, Cheng (Université d'Ottawa | University of Ottawa, 2006)
This paper focuses on the economic performances of the first-generation and second-generation immigrants in Canada using data from the 2001 Census. The results are consistent with the conclusions of previous studies. They show that both male and female fi